ANALISIS KETERBACAAN WACANA BUKU TEKS BAHASA ARAB KARANGAN "A. SYAEKHUDDIN, HALID AL-KAF DAN JALAL SUYUTI" BERDASARKAN STANDAR KRITERIA BSNP - Nurhakim, Anugrah (2016)
Buku ajar sangat penting bagi pendididkan, salah satunya adalah pelajaran bahasa Arab. Penelitian ini dilakukan pada siswa kelas VI SD IT Al-Amin Tahun Ajaran 2014-2015 terhadap buku karangan A. Syaikhuddin dkk. Dengan cara kualitatif, metode deskriptif analisis dan pendekatan naturalistik. Hasilnya adalah ;1) bahwa buku tersebut sesuai dengan kurikulum pemerintah yang dikembangkan oleh yayasan; 2) Hasil perhitungan menggunakan uji rumpan, memiliki tingkat keterbacaan 68% ; 3) Secara keseluruhan memenuhi kriteria buku teks menurut BSNP. Rekomendasi dari hasil penelitian ini adalah pemilihan buku teks yang tepat bagi seluruh jenjang pendidikan khususnya bagi jenjang sekolah dasar. ;Textbooks are very influential on students' understanding although the difference levels between students from one another. Therefore, the preparation of textbooks should be done carefully and precisely, because the preparation of textbooks that are not based on aspects of good textbooks would be very detrimental to the students. One of the formal education who have problems about Arabic language teaching materials are at the elementary level in which there are learning Arabic. Thus, this study was conducted on sixth graders of SDIT Al-Amin Academic Year 2014-2015 were using the book by A. Syaikhuddin et al. The study, conducted by researchers in line with the qualitative approach with descriptive methods of analysis are grooved in a naturalistic approach. Naturalistic approach in question is the ground situation is natural or reasonable, as is, without being manipulated. From this study it can be concluded that the book has a readability level of 68% and overall met the textbooks criteria according BSNP. Although it does not cause a loss in its use by students, but there are still many things to be improved and perfected.